The Relevance of The Song Lir-Ilir According to Ainun Najib (Cak Nun) for Character Education - Imamul Muttaqin, Muhammad; Khoirun Nisa' , Amelia; Nazwalina Vidiani , Aisya; Aulia Infazhah , Fia; Muzaki Munawar , Fuad; Balgista Habibilah, Mutiara (Mudir : Jurnal Manajemen Pendidikan, 2023)
This article aims to investigate the application of the values of the Tembang Lir-Ilir in moral education as an effort to overcome moral decline in the era of Society 5.0. The era of Society 5.0, characterized by the adoption of digital technology and artificial intelligence, has brought significant social changes in various aspects of human life. However, along with technological advancements, there has also been an alarming moral decline in society. This study uses the library research method by collecting data through a literature review of the values of the song Lir-Ilir applied in character education. The values of the tembang Lir-Ilir include ethics, morality, wisdom, unity, and love. The results showed that the application of the values of the song Lir-Ilir in moral education can make a positive contribution in overcoming moral decline in the era of Society 5.0. Moral education that integrates the values of tembang Lir-Ilir can help individuals develop strong character, good ethics, and a deeper understanding of their social rights and responsibilities. In addition, the application of the values of tembang Lir-Ilir can also promote unity and love among individuals, reduce social disparities, and encourage harmonious cooperation in society.